2005
DOI: 10.1111/j.1471-4159.2005.03416.x
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of microglial cells induced by 1‐methyl‐4‐phenylpyridinium in mesencephalic cultures results from an astrocyte‐dependent mechanism: role of granulocyte macrophage colony‐stimulating factor

Abstract: There is evidence that an inflammatory microglial reaction participates in the pathophysiology of dopaminergic neuronal death in Parkinson's disease and in animal models of the disease. However, this phenomenon remains incompletely characterized. Using an in vitro model of neuronal/ glial mesencephalic cultures, we show that the dopaminergic neurotoxin 1-methyl-4-phenylpyridinium (MPP Parkinson's disease (PD) is the second most common neurodegenerative disease after Alzheimer's disease (AD) and is associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Different experiments were carried out using cultures of astrocytes or dopaminergic neurons (cell line MES 23.5) or microglial cells (N9), taking into account that dopaminergic neurotoxins such as MPP þ act directly on dopaminergic neurons and astrocytes but indirectly on microglia (Henze et al, 2005), and that the previous experiments indicated that ER-a is responsible for the lack of neuroprotection of estrogen after LTED.…”
Section: Role Of Estrogen Receptors On Astrocytes Neurons and Micromentioning
confidence: 99%
“…Different experiments were carried out using cultures of astrocytes or dopaminergic neurons (cell line MES 23.5) or microglial cells (N9), taking into account that dopaminergic neurotoxins such as MPP þ act directly on dopaminergic neurons and astrocytes but indirectly on microglia (Henze et al, 2005), and that the previous experiments indicated that ER-a is responsible for the lack of neuroprotection of estrogen after LTED.…”
Section: Role Of Estrogen Receptors On Astrocytes Neurons and Micromentioning
confidence: 99%
“…In the brain, TNF␣ is a potent signal for the activation of both microglia and astroglia (76), and like IL-1␤, TNF␣ also robustly activates CN/NFAT signaling in astrocytes (26). GM-CSF appears to play a crucial role in amplifying the local microglial response in areas of neuronal damage and/or protein aggregation (77). Indeed, GM-CSF and other colonystimulating factors are powerful signals for microglial activation and subsequent release of IL-1␤ (78).…”
Section: Il-mediated Immune/inflammatory Signaling and The Cn/nfatmentioning
confidence: 99%
“…MPP + could stimulate the production of free radicals or ROS in neuronal cells; thus, this agent is commonly employed in neurological studies to induce oxidative and/or inflammatory injury [15][16][17] . Recently, several studies have demonstrated that MPP + stimulates the production of the superoxide radical in vitro and induces cell death in glial cells 18,19 . Here, we employed Raw 264.…”
Section: Discussionmentioning
confidence: 99%